Red Salak Cultivation Business in Efforts for Farmer Family Welfare in Riring Village, Taniwel District, West Seram Regency - Salakory, David Marthen; Noya, Josephus; Laturake, Philipus; Tupamahu, Yonette Maya (Agrikan Jurnal Agribisnis Perikanan, 2023)
This study aims to analyze aspects of red snake fruit cultivation by farmers and economic aspects including marketing, prices and income which have an impact on the welfare of red snake fruit farming families in Riring Village. Sampling in Riring Village was deliberately made up of 25 farmers based on the consideration of the criteria of productive age farmers. Data collection methods, namely observation and interviews and data were analyzed using descriptive qualitative. The results showed that the red snake fruit cultivation process in Riring Village was still conventional so that it affected the red snake fruit production in each harvest season. There are 2 marketing patterns for red salak in Riring Village, namely: Pattern I: Farmers → Collectors → Consumers, and Pattern II: Farmers → Retailers → Consumers. The price for harvesting red salak during the big harvest season ranges from Rp. 25,000.00 - Rp. 30,000.00 per kg while during the medium and small harvest periods it ranges from Rp. 30,000.00 - Rp. 45,000.00 per kg. The income of red snake fruit cultivating farmers in Riring Village is that during the big harvest season the income of snake fruit farmers ranges from Rp. 625,000.00 to Rp. 1,250,000.00, during the medium harvest season the farmers' income ranges from Rp. Thus the harvest and sales results have an impact on family welfare.